1991
DOI: 10.1177/000456329102800315
|View full text |Cite
|
Sign up to set email alerts
|

A Sandwich Enzyme-Linked Immunosorbent Assay for β2-Glycoprotein I

Abstract: SUMMARY.A solid-phase sandwich enzyme-linked immunosorbent assay for determining 0,-glycoprotein I in urine has been developed. It has a working concentration range of 5-40 pg/L and a detection limit of approximately 1 . 4 pg/L. The withinplate coefficient of variation (CV) falls between 1.4% and 2 -1 % , and the betweenbatch CV ranges from 5.2 to 6.0%. Recovery of P,-glycoprotein I added to urine varies between 96 and 110%. The assay can also be used for determining P,-glycoprotein I in serum. Additional key … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1991
1991
2006
2006

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Previous work in our own laboratory has shown that urinary f32G I dilutes in parallel with purified serum standard up to a level of around 40 /lg/L, 13 although the exact level depends on the individual urine. Unfortunately, the only commercial standard available is purified from plasma rather than urine.…”
Section: Discussionmentioning
confidence: 89%
“…Previous work in our own laboratory has shown that urinary f32G I dilutes in parallel with purified serum standard up to a level of around 40 /lg/L, 13 although the exact level depends on the individual urine. Unfortunately, the only commercial standard available is purified from plasma rather than urine.…”
Section: Discussionmentioning
confidence: 89%
“…31,[44][45][46][47][48][49][50][51] Interestingly, a significant positive correlation was observed between age and serum ␤2GPI levels in healthy individuals. This is in agreement with previous reports [45][46][47][48][49][50][51] that showed that older healthy individuals have significantly higher serum ␤2GPI concentrations than their younger counterparts. The higher levels associated with increasing age could indicate increasing synthesis of ␤2GPI or reduced catabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Then 100 iLL of diluted samples and standards (l:20 dilution in PBS containing 1% Tween 20) were added in duplicate to appropriate wells. To reduce inter-well variability, the arrangement described by Sansom et al 13 was adopted. After incubation at 4°C overnight, plates were then washed as described above and 100 iLL peroxidase conjugated antibody (1:500 dilution in PBS/I % Tween 20) added to each well.…”
Section: Methodsmentioning
confidence: 99%